A study of hypertension among tribal adults in a block of Mandla district, Madhya Pradesh, India - Kumar, Rahul Kewal; Tyagi, Asha Ram; Tiwari, Rajesh; Rai, Neeraj (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is one of the most Important Public Health challenges worldwide. In India, there is no composite estimate on prevalence of hypertension among indigenous tribes, but the increasing prevalence of hypertension across the time among tribes has been observed by independent researchers. Further studies among the tribal population may reduce morbidity & mortality patterns, also ample avenues of prevention of such silent killer disease could well be explored. We did this study to find out the Magnitude of Hypertension and Pre Hypertension among Tribal adults with associated risk factors. Methods:A cross sectional study using Multi stage Sampling Method with house to house visits & study was conducted in Narayanganj block of Mandla District during 1st October to 30th September 2015. Sample size came out to be 300. Personal Interview, Anthropometric measurements & Clinical Examination was done and a Pre-designed Questionnaire form was filled from every study subject. Analyzed on SPSS (Version 20, IBM, USA). Results: The Magnitude of hypertension and Pre Hypertension was found at 22.0% and 32.7 % respectively in tribal subjects. The association of Hypertension with increasing Age was found to be significant (P< 0.001). Association of gender and hypertension was significant showing association of hypertension with tribal males. P< 0.001.The association of hypertension with alcohol Consumption was significant. P = 0.0050. Conclusions:Hypertension & Pre hypertension is increasing in tribals. The disorder is mostly silent and needs to be addressed at this incipient stage to prevent its long term effects.